2022
DOI: 10.1007/s11356-022-22270-y
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of neonicotinoid insecticides in global surface waters

Abstract: Neonicotinoids (NEOs) are a class of insecticides that have high insecticidal activity and are extensively used worldwide. However, increasing evidence suggests their long-term residual in the environment and toxic effects on nontarget organisms. NEO residues are frequently detected in water and consequently have created increasing levels of pollution and pose signi cant risks to humans. Many studies have conducted surveys of NEO concentrations in water; however, few studies have focused on global systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 44 publications
0
5
0
3
Order By: Relevance
“…Neonicotinoid insecticides are the most widely used synthetic insecticides in the world [ 24 ]. Due to their water solubility and long-term persistence in the environment, they have caused serious environmental problems [ 25 ]. Insecticides can enter the body through ingestion, inhalation, or skin contact [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neonicotinoid insecticides are the most widely used synthetic insecticides in the world [ 24 ]. Due to their water solubility and long-term persistence in the environment, they have caused serious environmental problems [ 25 ]. Insecticides can enter the body through ingestion, inhalation, or skin contact [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the IMI acute EC50 value was definitely above the concentrations of environmental concern, going from hundredths of nanomoles/L to tenths of micromoles/L [ 26 , 28 , 39 , 40 , 41 ], and that the aquatic organisms are exposed to IMI residues for a prolonged period of time, we decided also to evaluate the long-term toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the toxicity data obtained in this study indicates that, as previously concluded for sh, IMI and TIA do not present a risk of acute or subchronic mortality for amphibians in larval stages in nature, because the concentrations causing mortality (Tables 1 and 2) are well above the concentrations normally reported in aquatic environments. Indeed, these usually range between 0.004-9140 ng/L (mean 119.5 ng/L) for IMI and 0.002-3820 ng/L (mean 59.7 ng/L) for TIA, according to a recent meta-analysis of worldwide eld data (Wang et al, 2022). Similarly, in the Pampa region, the highest concentrations of IMI measured so far were 430 and 560 ng/L (Caprile, 2019;Perez et al, 2017), while no values were found for aquatic concentrations of TIA in the Pampa.…”
Section: Discussionmentioning
confidence: 99%